Pengolahan Citra untuk Peningkatan Kontras dengan Fungsi GST (Gray Scale Transformation) - sri siswanti (Jurnal Ilmiah SINUS, 2010)
Image processing is basically done by modifying each point in the image as needed. The contrast of light and dark states in an image.Gray Scale Transformation (GST) has a function to map the input level of gray (Ki) to the image of a gray image of the output (Ko) Ko = f (Ki). The principle of increasing the contrast with the increase in GST is to make the point that tends to become darker to be more darkness and darker which tend to be more brilliant light.Keywords : image processing, contrast, Gray Scale Transformation